Transitional policies and durable solutions for displaced Kashmiri Pandits - Rajput, S (Refugee Studies Centre, University of Oxford, 2016)
The continuation of the predicament of those who remain displaced from the Kashmir Valley since 1989 results from the unintended consequences of past policies. Transitioning from the ‘temporary’ policies that keep the displaced communities intact in ‘safe zones’ to policies that aim to secure long-term solutions presents moral dilemmas for policymakers.